Integrating Context Knowledge With Concepts Ontology For Handling Lexical Semantic Ambiguity Of Natural Language Interface In Question Answering (QA) System - Omar Mohammad Hilal Alharbi
Question Answering(QA) Systems allow the user to ask questions in a natural language and obtain an exact answers. In general, the QA system is composed of four modules, they are namely: question processing, documents processing, passages processing, and answer processing. Question processing module is considered the most fundamental component in the natural language interface of the QA system, and its quality impacts the performance of the overall QA system. This module receives natural language questions (NLQs). The most difficult problem in developing a QA system is so hard to find an exact answer to the NLQ. One of the most challenging problems in returning answers is how to resolve lexical semantic ambiguity in the NLQs. Lexical semantic ambiguity may occurs when a user's NLQ contains words that have more than one meaning. As a result, QA system performance can be negatively affected by these ambiguous words. In this research, we aim to resolve this problem by introducing CKCO (Context Knowledge & Concepts Ontology) approach. This approach integrates context knowledge and concepts ontology of the proposed domain, into a shallow natural language processing (SNLP) technique. Concepts ontology represents real world facts that describe the proposed domain, while context knowledge contains a set of words with their senses obtained from WordNet Domain and a group of words within the proposed domain serve as context labels, and it is determined based on neighborhood words in the NLQ. SNLP technique includes shallow syntactic analysis based on chunking method, and shallow semantic analysis using semantic role labeling method. Experimental results show that CKCO approach has 78.2% accuracy on a test set of 150 NLQs. We applied CKCO approach to a QA prototype in a university domain for new students to examine the impact of our approach in retrieving correct answers. The QA prototype was evaluated based on two aspects: prototype performance and acceptance of users. Experimental results show that the CKCO approach together with other components of our QA system yield a result which is 77.3% for accuracy which is 4.7% above the accuracy yielded by the same prototype without disambiguation. Acceptance aspect was evaluated based on its user's perspective, to determine the perceived ease of use (PEU), perceived satisfaction (PS), and perceived usefulness (PU) of the QA system that we developed. The results from the respondents reflect that our QA prototype was acceptable.